Graphene: Layer‐Stacking Growth and Electrical Transport of Hierarchical Graphene Architectures (Adv. Mater. 20/2014). (May 2014) - Luo, Birong; Chen, Bingyan; Meng, Lan; Geng, Dechao; Liu, Hongtao; Xu, Jie; Zhang, Zhiyong; Zhang, Hantang; Peng, Lianmao; He, Lin; Hu, Wenping; Liu, Yunqi; et al.
<x xml:space="preserve">Abstract</x> A layered stacking growth route for the hierarchical assembly of graphene on a liquid copper catalyst by chemical vapor deposition is described by G. Yu and co‐workers on page 3218. These hierarchical graphene architectures, displaying a snow‐like morphology, reveal the non‐equilibrium growth processes of multi‐layer graphene and present electrical anisotropy. This work potentially offers impetus for the application of graphenebased electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>